Reforma Tributária: Os impactos da CBS instituída pela Emenda Constitucional n° 132/2023 sobre a Zona Franca de Manaus - Ferreira, Paula Queiroz (2024)
This article intends to analyze the repercussion of the new tax provided for in art. 195, V, of the Federal Constitution, the Social Contribution on Goods and Services (CBS) on activities relevant to the Free Economic Zone of Manaus (ZFM), which was included by Constitutional Amendment 132/2023, and replaces the Social Integration Program (PIS), the Contribution for Social Security Financing (COFINS) and the Tax on Industrialized Products (IPI). The objective is to verify the impacts of the new tax on ZFM, focusing on the guarantees arising from EC 132/2023, thus seeking to verify the maintenance of the competitiveness of its products. During the development of the work, legal texts pertinent to the topic were examined, as well as relevant articles, using descriptive and qualitative research, in order to conclude that there is still no data that accurately determines all the repercussions of the incidence of CBS in the ZFM, however, even with the institution of the Tax Reform, some advantages relating to the ZFM will be maintained.